When day seven strikes: a cautionary tale of direct oral anticoagulation resumption following thyroidectomy - Phyoe, Swe Z.; Diab, Jason; Garibotto, Natalie (International Surgery Journal, 2026)
Delayed neck haematoma following thyroidectomy is an uncommon but potentially life-threatening complication due to the risk of rapid airway compromise. We report a 62-year-old man with non-valvular atrial fibrillation on rivaroxaban who developed a large anterior neck haematoma on postoperative day (POD) 7, three days after resumption of anticoagulation following an initially uncomplicated total thyroidectomy with lateral neck dissection. Emergency re-exploration revealed active bleeding from a small superficial vessel between the sternocleidomastoid and platysma. The patient recovered without further complications after evacuation, haemostatic adjuncts and delayed reintroduction of anticoagulation. This case highlights the potential for clinically significant delayed haemorrhage after thyroidectomy in the context of direct oral anticoagulation (DOAC) therapy. It also emphasises the importance of vigilant post-discharge counselling regarding late warning signs and supports individualised perioperative anticoagulation strategies in head and neck surgery.